BK polyomavirus genotypes represent distinct serotypes with distinct entry tropism - Pastrana, Diana V; Ray, Upasana; Magaldi, Thomas G; Schowalter, Rachel M; Çuburu, Nicolas; Buck, Christopher B (Journal of virology, 2013)
BK polyomavirus (BKV) causes significant urinary tract pathogenesis in immunosuppressed individuals, including kidney and bone marrow transplant recipients. It is currently unclear whether BKV-neutralizing antibodies can moderate or prevent BKV disease. We developed reporter pseudoviruses based on seven divergent BKV isolates and performed neutralization assays on sera from healthy human subjects. The results demonstrate that BKV genotypes I, II, III, and IV are fully distinct serotypes. While nearly all healthy subjects had BKV genotype I-neutralizing antibodies, a majority of subjects did not detectably neutralize genotype III or IV. Surprisingly, BKV subgenotypes Ib1 and Ib2 can behave as fully distinct serotypes. This difference is governed by as few as two residues adjacent to the cellular glycan receptor-binding site on the virion surface. Serological analysis of mice given virus-like particle (VLP)-based BKV vaccines confirmed these findings. Mice administered a multivalent VLP vaccine showed high-titer serum antibody responses that potently cross-neutralized all tested BKV genotypes. Interestingly, each of the neutralization serotypes bound a distinct spectrum of cell surface receptors, suggesting a possible connection between escape from recognition by neutralizing antibodies and cellular attachment mechanisms. The finding implies that different BKV genotypes have different cellular tropisms and pathogenic potentials in vivo. Individuals who are infected with one BKV serotype may remain humorally vulnerable to other BKV serotypes after implementation of T cell immunosuppression. Thus, prevaccinating organ transplant recipients with a multivalent BKV VLP vaccine might reduce the risk of developing posttransplant BKV disease.